The role of librarians in socio-economic and national development/ Mujahid Abu Bakar - Abu Bakar, Mujahid (2012)
Library service is an integral part of a country's general progress. It is one of the most efficient means of acquiring, organizing and makin available on democratic basis informational and educational materials. There was no argument that libraries really play big role towards national education and national development. The libraries are the main institution that provides information to education either for student or layman. The jobs created by the libraries also have improving a national economic. National development is directly and indirectly effected by the libraries functions. A knowledge society is one of the great contributions by the libraries that help national development keep growing and continually serve the people the best as they could.